Relationship between triglyceride glucose-body mass index baselines and variation with future cardiovascular diseases risk in the middle-aged and elderly individuals - Qiao, Junpeng; Chen, Xueyu; Pang, Jinhong; Fei, Haicheng; Liu, Zhang; Cheng, Fang; Chen, Qiaoqiao; Zhao, Yingying; Shi, Fengxue; Jia, Hongying; Chi, Weiwei (Frontiers in Endocrinology, 2025)
BackgroundCardiovascular diseases (CVDs) are gradually becoming the leading cause of morbidity and mortality among chronic non-communicable diseases. Previous studies have found that the TyG index is an effective alternative indicator for insulin resistance (IR) and is associated with cardiovascular events. Additionally, obesity directly or indirectly increases the risk of developing CVDs. Up to now, studies on the combined effects of these factors are insufficient, and the conclusions are not yet consistent. This study aims to analyze whether the baseline levels and fluctuations of triglyceride glucose-body mass index (TyG-BMI) are associated with the incidence of CVDs and their subtypes in a prospective cohort of middle-aged and elderly individuals.MethodsThe data for this study were obtained from the China Health and Retirement Longitudinal Study (CHARLS), which is an ongoing nationally representative prospective cohort study. After excluding participants with partially missing variables that could affect the study results, this study ultimately included 7,072 participants, with data records spanning from 2011 to 2020. The exposures were TyG-BMI and the change in TyG-BMI from 2011 to 2015. The TyG-BMI index was calculated as TyG index multiply BMI. The change of TyG-BMI was categorized using K-means clustering and baseline TyG-BMI was grouped based on quartiles. We used Cox proportional hazards models to evaluate the relationship between baseline quartiles of the TyG-BMI index and its variability with CVDs and their subtypes.ResultsAmong the 7,072 participants (mean age of 59.1 ± 9.3 years), 3330 (47%) were male. During an average follow-up of 7.1 years, 1,774 (25.1%) participants developed new-onset cardiovascular diseases. After stratification by baseline TyG-BMI quartiles, higher TyG-BMI levels were associated with an increased risk of CVDs, The hazard ratio (HR) and 95% confidence interval (95% CI) for the highest quartile group were 1.69 (1.44-2.00). After adjusting for potential confounding factors, compared to participants with consistently low TyG-BMI levels, those with moderate TyG-BMI levels and a slowly increasing trend had an HR of 1.27 (95% CI 1.10-1.47), while those with the highest TyG-BMI levels and a slowly decreasing trend had an HR of 1.52 (95% CI 1.26-1.83).ConclusionMaterial changes in the TyG-BMI are independently associated with the risk of CVDs in middle-aged and elderly individuals. Detecting long-term changes in the TyG-BMI may aid in the early identification of high-risk individuals and help prevent the occurrence of various cardiovascular diseases.